Dual Lex: applying logistics strategies in the educational process - Khistyeva, Daryna; Pócsová, Jana (Frontiers in Education, 2024)
This article discusses the landscape of education. The challenge lies in harmoniously blending the directive PUSH strategies, which focus on structured guidance, with the exploratory PULL methods, centered around the learner's initiative. To illustrate this, the realms of science and art as examples are used, showcasing how these strategies can be interpreted and applied in different educational contexts. The educational systems of selected countries are considered from the viewpoint of the novel framework involving PUSH and PULL methodologies in the delivery of education. China's emphasis on a structured and orderly educational process, Finland's dedication to student autonomy and flexibility, and the UK's integrative, hybrid model. Nevertheless, there is still a need for a cohesive approach that effectively combines the structured science education methods with the more fluid and interpretative methods used in art education. This paper deals with a comparative analysis of how educational systems in China, Finland, and the UK navigate the PUSH-PULL dynamics. In this article, we propose and develop a new model for understanding the role of students in the educational system. This model, which we are introducing, views the student in a dual capacity: as both an integral part of the larger educational framework and as the primary consumer of state-provided knowledge. Our model aims to reframe the traditional perspective on students' roles in education. By introducing the "Dual Lex" concept, this study aims to merge (melt) two principal different educational models into a cohesive whole. The term "Dual" emphasizes the simultaneous use of these two methodologies, while "Lex" suggests a set of principles or rules governing this integration. Overall, this approach seeks to establish an educational framework that is as methodical and precise as it is creative and expressive, thereby equipping students with the skills and knowledge for a versatile and dynamic educational journey and more flexible and student-centered preparation for their future professional careers.